Production and evaluation of guidelines for the management of inflammatory bowel disease: the Leicester experience. Issue 881 (1st March 1999) - Read, A M; Stone, M A; Rathbone, B J; de Caestecker, J; Wicks, A C B; Longworth, S; O'Shea, C R; Baker, R; Spence, D; Hall, A W; Kelly, M J; Cannon, J; et al.
Abstract : Consensus guidelines for the management of patients with inflammatory bowel disease were produced by gastroenterologists, gastrointestinal surgeons and a cross-section of general practitioners (GPs) from Leicestershire in order to develop a seamless pattern of care with a common approach to diagnosis and treatment. It was hoped that the guidelines would encourage a movement towards care in the community for many patients with stable disease and so speed up new consultation rates. The study then assessed the impact of these guidelines on the referral letters of GPs to hospital consultants, the prediction of disease and adherence to them on re-referring patients after discharge. The guidelines were distributed to all 487 GPs in the Leicester Health Authority area and the gastroenterology teams within the hospitals. The value of the guidelines was assessed by an audit of referral letters, the length of time from referral letter to out-patient appointment, both before and after the launch of the guidelines, adherence to the guidelines on re-referral, and monitoring the outcome of the discharged patients. Whilst the guidelines may have helped GPs to manage stable patients in the community, the content of referral letters and the diagnostic abilities of GPs were not seen to improve since the launch of the guidelines. However, only 5% of stable patients who were discharged from one clinic were re-referred for inflammatory bowel disease.